KONSEP DASAR PENDIDIKAN INKLUSI: LANDASAN FILOSOFIS, PRINSIP, DAN IMPLEMENTASINYA DALAM SISTEM PENDIDIKAN - Muhammad Mukhlas Adi Putra PUTRA; Muhammad Hasan Noufal; Ahmad Agus Sholehuddin; M. Mahbubi (As-Sulthan Journal of Education, 2026)
Inclusive education is an educational paradigm that positions every individual regardless of physical, intellectual, social, emotional, or cultural background as a subject entitled to education within a shared learning environment. This article aims to comprehensively examine the fundamental concepts of inclusive education, including its historical development, philosophical and legal foundations, operational principles, as well as the challenges and strategies for its implementation in Indonesia. The study employs a literature review approach by analyzing various relevant academic sources. Historically, the concept of inclusive education emerged from the integration movement for children with special needs in the 1970s and was later reinforced by the 1994 Salamanca Statement, which affirmed every child's right to learn together without discrimination. In Indonesia, the legal foundation is reflected in the 1945 Constitution, the National Education System Law, and Ministerial Regulation No. 70 of 2009 on inclusive education. Philosophically, inclusive education is rooted in the values of social justice, respect for human dignity, and the recognition of diversity as a strength rather than an obstacle. Its operational principles include curriculum flexibility, differentiated instruction, collaboration between regular teachers and special assistant teachers, as well as active participation from parents and the community. Nevertheless, implementation in the field still faces serious obstacles, including teachers' limited understanding of differentiated teaching strategies, inadequate physical accessibility facilities, social attitudes that remain less than fully inclusive, and uneven distribution of resources across regions. Strengthening strategies needed include continuous professional development for educators, reinforcing the role of school-based disability service units, formulating more operational policies at the school-unit level, and engaging communities to build collective awareness of the importance of diversity. The findings indicate that the success of inclusive education does not rely solely on formal regulations, but requires a fundamental paradigm shift in how society perceives difference, the readiness of educators, and the provision of adequate systemic support. Inclusive education is not merely a policy project but a reflection of a nation's moral commitment to justice and respect for human diversity.